2010
DOI: 10.1186/1471-244x-10-83
|View full text |Cite
|
Sign up to set email alerts
|

Convergent validity of K-SADS-PL by comparison with CBCL in a Portuguese speaking outpatient population

Abstract: BackgroundDifferent diagnostic interviews in child and adolescent psychiatry have been developed in English but valid translations of instruments to other languages are still scarce especially in developing countries, limiting the comparison of child mental health data across different cultures. The present study aims to examine the convergent validity of the Brazilian version of the Schedule for Affective Disorders and Schizophrenia for School-Age Children/Present and Lifetime Version (K-SADS-PL) by compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 22 publications
5
35
0
7
Order By: Relevance
“…The first indicated high sensitivity of the instrument in comparison with psychiatric assessment: 87% of the clinical cases were identified (Bordin, Mari, & Caiero, 1995). This was confirmed in comparison with results found using a semi-structured psychiatric interview (K-SADS-PL): 82.4% of children with psychiatric disorders achieved clinical scores on the CBCL (Brasil & Bordin, 2010). Using the latest version of the CBCL, Rocha et al (2013) reported the validity of its factorial structure (RMSEA = .023), the discriminative capacity of the instrument (p < .001), and suggested more appropriate normative standards for assessing our population.…”
Section: Instrumentssupporting
confidence: 81%
“…The first indicated high sensitivity of the instrument in comparison with psychiatric assessment: 87% of the clinical cases were identified (Bordin, Mari, & Caiero, 1995). This was confirmed in comparison with results found using a semi-structured psychiatric interview (K-SADS-PL): 82.4% of children with psychiatric disorders achieved clinical scores on the CBCL (Brasil & Bordin, 2010). Using the latest version of the CBCL, Rocha et al (2013) reported the validity of its factorial structure (RMSEA = .023), the discriminative capacity of the instrument (p < .001), and suggested more appropriate normative standards for assessing our population.…”
Section: Instrumentssupporting
confidence: 81%
“…As an upshot, validity and reliability data for specific K-SADS-PL diagnoses are scant. In a Brazilian clinical sample, the authors found support for convergent validity of any diagnosis and any disruptive diagnosis, but not for any affective/anxiety diagnosis (11). This study only examined broad diagnostic categories without considering specific diagnoses.…”
Section: Introductionmentioning
confidence: 80%
“…63 All of them have been validated in Brazil, and, as mentioned before, do not provide a definitive diagnosis, but may suggest comorbidities, and allow symptom follow-up. [64][65][66] Treatment Pharmacological treatment in children and adolescents with BD is mandatory not only in the acute phase that may involve crisis stabilization for psychosis, suicidal behavior or agitation, but also to prevent relapses and recurrences. The mainstay for the management of BD is the use of medication along with enhancement of social skills and family support.…”
Section: Diagnosismentioning
confidence: 99%